Combined microwave and hot air convective dehydration on physical and biochemical qualities of dried longan flesh - P. Chaikham (2018)
The effect of microwave radiation densities (100 and 300 W) and hot air velocities (5 and 10 m/s) on the physical and biochemical properties as well as consumer acceptability of dried longan fleshes was investigated. It was found that the moisture in the longan dried by microwave-air convective oven was displaced faster than the traditional drying. The firmnesses of longan dried at 300 W were higher than those in longan dried at 100 W. The loss of lightness (L parameter) or the increase of redness (a * parameter) in longan dried at 300 W could be associated with the increase of Maillard browning and caramelization reactions. Lowest microwave power density could be preserved total phenolic compounds, gallic acid and ellagic acid in the products greater than conventional- and high microwave power-drying techniques. Panelists were most satisfied with sensory qualities of the dried longan using microwave power 100 W with air velocity 5 and 10 m/s. It was concluded that drying at 100 W and air velocity 5 m/s was acceptable for the production of dried longan fleshes.